Analysis of Publicly Available Business E-Data in Slovakia - Hricová, Romana; Adamčík, Stanislav (EAI Endorsed Transactions on Smart Cities, 2018)
The paper analyzes publicly available e-data that entrepreneurs need and use for their business in Slovakia. Today is not the problem of getting to the information, but getting to it as quickly as possible, the cheapest and, most importantly, getting it as accurately as possible. Although data has been published in various forms and public institutions in the past, a major shift has been made by launching the slovensko.digital platform. The aim of this initiative is to improve informatization in Slovakia. The ambition of the article is to point out what e-data is being provided today and what are the ways to use it.
Keywords: E-Data; Consolidation; Dataset; Information